Schema and solutions for decentralised multi-project scheduling problem. (1st January 2013) - Wang, Lei; Zhan, Dechen; Nie, Lanshun; Xu, Xiaofei
Decentralised multi-project scheduling problem is an extension of multi-project scheduling problem, and it has several different characteristics from traditional multi-project scheduling problem from centralised decision making viewpoint. Unfortunately, existing studies on this problem are scarce and usually focused on one special issue of the problem. Based on the definition and analysis on the characteristics of decentralised multi-project scheduling problem, we propose an α | β | γ schema for this problem from three fields of decision maker, decision mode and coordination objective, which would help researchers to position their solutions in the schema, and compare their work with others conveniently. Then, based on the schema proposed, we review the existing studies and solutions for decentralised multi-project scheduling problem in the literature. Finally we present several directions of this problem for the future research.